2008
DOI: 10.1029/2007tc002160
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of the Selkirk fan, southeastern Canadian Cordillera: A composite Middle Jurassic–Cretaceous orogenic structure

Abstract: The eastward transition from penetrative ductile deformation, metamorphism, and plutonism in the hinterland of the southern Canadian Cordillera to the “thin‐skinned” deformation of the foreland represents a significant change in tectonic style and process. The transition is also marked by a zone of structural divergence across which SW vergent hinterland structures pass into NE vergent foreland structures. The Selkirk fan within the Selkirk Mountains of the southern Canadian Cordillera is considered a type loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 80 publications
(118 reference statements)
1
21
0
Order By: Relevance
“…Southwest directed thrusting within Stikinia and Cache Creek terrane (Figure ) is considered to indicate Middle Jurassic linkages with southwest vergent folding and thrusting in the parautochthonous Omineca belt of southern British Columbia [ Evenchick et al ., ]. By late Middle to early Late Jurassic time, some hinterland structural styles had switched from southwest to northeast vergent and likely record the cratonward propagation of the retroarc thrust system in Yukon and southeastern British Columbia [e.g., Crowley and Brown , ; Colpron et al ., ; Gibson et al ., , ; Staples et al ., , ]. Peak Barrovian metamorphism associated with this retroarc deformation occurred ~170–160 Ma in southern Omineca belt of British Columbia [e.g., Parrish , ; Evenchick et al ., ], and regional orogenic gold veins that are characteristic of very late to postpeak metamorphic conditions [ Goldfarb and Groves , ] were emplaced into the northern Omineca belt of Yukon by the early Late Jurassic (Figure ) [ Allan et al ., ; Bailey , ].…”
Section: Discussionmentioning
confidence: 99%
“…Southwest directed thrusting within Stikinia and Cache Creek terrane (Figure ) is considered to indicate Middle Jurassic linkages with southwest vergent folding and thrusting in the parautochthonous Omineca belt of southern British Columbia [ Evenchick et al ., ]. By late Middle to early Late Jurassic time, some hinterland structural styles had switched from southwest to northeast vergent and likely record the cratonward propagation of the retroarc thrust system in Yukon and southeastern British Columbia [e.g., Crowley and Brown , ; Colpron et al ., ; Gibson et al ., , ; Staples et al ., , ]. Peak Barrovian metamorphism associated with this retroarc deformation occurred ~170–160 Ma in southern Omineca belt of British Columbia [e.g., Parrish , ; Evenchick et al ., ], and regional orogenic gold veins that are characteristic of very late to postpeak metamorphic conditions [ Goldfarb and Groves , ] were emplaced into the northern Omineca belt of Yukon by the early Late Jurassic (Figure ) [ Allan et al ., ; Bailey , ].…”
Section: Discussionmentioning
confidence: 99%
“…5) preserves evidence of penetrative shortening throughout the Late Jurassic to Paleocene (Currie, 1988;Ferguson, 1994;Digel et al, 1998;Reid, 2003;Ghent and Simony, 2005;Gibson et al, 2008). Continued growth of the Omineca highland, as it was translated inboard onto thicker, more rigid crust, loaded the lithosphere and affected the sedimentation patterns of the adjacent basin to the east.…”
Section: Late Middle Jurassic To Earliest Cretaceous Orogen Buildup Amentioning
confidence: 99%
“…Monger et al ., ; Nelson et al ., ; Colpron et al ., ; Beranek & Mortensen, ). In the Mesozoic, the orogen grew as a consequence of protracted compression and crustal thickening during arc‐continent collisions (e.g., Berman et al ., ; Gibson et al ., ) as the North American craton moved westward, converging with its offshore subduction zone (Monger & Price, ). In the southern Canadian Cordillera, a significant body of geochronological data from the metamorphic core of the orogen has revealed that despite similarities in regional metamorphic grade and deformation patterns, both were strongly diachronous, younging systematically with increasing structural depth (Parrish, ).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Parrish (), Brown () and Gibson et al . () have all attributed this downward younging tectonism in the southeastern Canadian Cordillera to the progressive incorporation and burial of material as the burgeoning orogen propagated northeastward towards the foreland.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation